2020
DOI: 10.1002/bse.2666
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐emotional wealth and corporate responses to environmental hostility: Are family firms more stakeholder oriented?

Abstract: Do family firms care more for different stakeholders than nonfamily firms when operating in a hostile business environment? This study addresses this question and fills the existing void in family business research. It shows that family‐controlled firms adopt corporate social responsibility strategies and balance the demands of internal and external interest groups to preserve their socio‐emotional wealth while facing fierce competition, resource scarcity, and penurious economic conditions. More specifically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 82 publications
(146 reference statements)
0
51
0
5
Order By: Relevance
“…In a recent study, García-Sánchez et al (2020) examine an international sample of 956 listed firms and show that FFs show a higher level of CSR performance compared to non-FFs. Abeysekera & Fernando (2020) analyze firms in the US and observe that FFs are more responsible to shareholders than non-FFs in engaging in environmental investments.…”
Section: Family Vs Non-family Firmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, García-Sánchez et al (2020) examine an international sample of 956 listed firms and show that FFs show a higher level of CSR performance compared to non-FFs. Abeysekera & Fernando (2020) analyze firms in the US and observe that FFs are more responsible to shareholders than non-FFs in engaging in environmental investments.…”
Section: Family Vs Non-family Firmsmentioning
confidence: 99%
“…The literature on CSR in FFs focuses both on developed and emerging countries, as shown in Figure 13. The empirical setting in 29 studies is the US (Cordeiro et al, 2020;Cui et al, 2018;Liu et al, 2017), 22 studies focused on multicountry contexts (Bansal et al, 2018;García-Sánchez et al, 2020;Martínez-Ferrero et al, 2017), 18 are based in Italy (Gavana et al, 2017a(Gavana et al, , 2017bVenturelli et al, 2021), nine in Taiwan (Huang et al, 2016), and China (Zhou, 2014), eight in Spain (Hernández-Perlines & Rung-Hoch, 2017)) and six in India (Bhatnagar et al, 2019;Cordeiro et al, 2018), four are based in Germany (Britzelmaier et al, 2015), Indonesia (Nirmala et al, 2020), Korea (Choi et al, 2019), Malaysia (Othman et al, 2011), and in France Nekhili et al, 2017), three are based in the Netherlands (Graafland et al, 2003), and Pakistan (Shahzad et al, 2018).…”
Section: Empirical Settingsmentioning
confidence: 99%
“…In general, the literature argues that family firms' interests are associated with socioemotional wealth and, therefore, they perceive more benefits than risks from CSR (i.e., Berrone et al 2010;Cruz et al 2014;Cuadrado-Ballesteros et al 2015García-Sánchez et al 2021a). For that reason, their commitment to CSR is usually higher, which would justify the idea that they will be less prone to CSR decoupling practices.…”
Section: Theoretical Framework and Research Hypothesismentioning
confidence: 99%
“…This perspective of family firms suggests a more significant commitment to Corporate Social Responsibility (CSR) by favouring the transfer of the firm to future generations (Kim et al 2016;Binz et al 2017) and reinforcing the success and image of the company (Sharma and Sharma 2011). Although the literature is not unanimous, it can be argued that most of the time, but not always, they are socially and environmentally more responsible than other companies (i.e., Berrone et al 2010;Cennamo et al 2012;Cruz et al 2014;Campopiano et al 2014;Marques et al 2014;Cuadrado-Ballesteros et al 2015Martínez-Ferrero et al 2016;Feliu and Botero 2016;Samara and Berbegal-Mirabent 2018;García-Sánchez et al 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Stavrou et al (2007) and Cruz et al (2010) have reported that the employees of family firms enjoy greater job stability and better working conditions, while Cuadrado-Ballesteros et al (2017) and Gavana et al (2019) highlight these firms' greater commitment to philanthropic activities and ethical issues. Dyer and Whetten (2006) and Bingham et al (2011) supply preliminary evidence that the activities of family businesses are significantly less harmful, socially and environmentally, and other studies have reported that family firms present a greater predisposition towards CSR (Chrisman et al 2007;Dyer and Whetten 2006;Cennamo et al 2012;Campopiano and De Massis 2015;García-Sánchez et al 2020c). Finally, these firms are characterised by qualities such as ethical commitment (O'Boyle et al 2010;Kidwell et al 2012), benevolence (Hauswald and Hack 2013) and integrity, empathy, warmth, courage, awareness and zeal (Payne et al 2011) among other emotional intelligence characteristics (Minárová et al 2020).…”
Section: Female Directors and Csr In The Family Firm: The Moderating Effect Of The Organisational Environmentmentioning
confidence: 83%